2007
DOI: 10.1002/mas.20135
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated metal ions in the gas phase

Abstract: Studying metal ion solvation, especially hydration, in the gas phase has developed into a field that is dominated by a tight interaction between experiment and theory. Since the studied species carry charge, mass spectrometry is an indispensable tool in all experiments. Whereas gas-phase coordination chemistry and reactions of bare metal ions are reasonably well understood, systems containing a larger number of solvent molecules are still difficult to understand. This review focuses on the rich chemistry of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 237 publications
(251 reference statements)
9
155
0
1
Order By: Relevance
“…As discussed above, the data of Lebouil et al [27] are consistent with the unipositive Mg + reaction sequence, and also with their proposed reaction sequence, which also involved a dissolution reaction, in their proposal, the dissolution reaction is Eq. (8 [40] implies that Mg + is unstable in the presence of water, and so is consistent with other studies [11][12][13][14][15] of the Mg + species.…”
Section: Williams Mcmurray and Co-workers [23-25] Used The Elegant Ssupporting
confidence: 88%
See 1 more Smart Citation
“…As discussed above, the data of Lebouil et al [27] are consistent with the unipositive Mg + reaction sequence, and also with their proposed reaction sequence, which also involved a dissolution reaction, in their proposal, the dissolution reaction is Eq. (8 [40] implies that Mg + is unstable in the presence of water, and so is consistent with other studies [11][12][13][14][15] of the Mg + species.…”
Section: Williams Mcmurray and Co-workers [23-25] Used The Elegant Ssupporting
confidence: 88%
“…However, gas phase studies have shown that Mg + reacts spontaneously with water in micro-seconds [11][12][13][14][15]. Moreover, Mg + is involved in the production of Grignard reagents [16], and Mg + is also common in stars as MgH [17].…”
Section: Issues To Be Addressedmentioning
confidence: 99%
“…1 Due to the complexity of solution phase chemistry, the study of the intrinsic interaction between the metal and water is simplified by gas phase analysis. In particular, gas phase electronic spectroscopy experiments reveal information about a metal's electronic configuration and its effects on the ion's overall metal-water structure, including the metal-water bond.…”
Section: Introductionmentioning
confidence: 99%
“…Their properties have been investigated in considerable detail, with a wide range of experimental techniques, as reviewed recently [2][3][4][5][6][7]. Photodissociation in the O-H stretch region of the infrared, often coupled with tagging with a weakly bound species like Ar, is the most widely used spectroscopic method [8][9][10][11][12][13][14] [15] were characterized with infrared spectroscopy by Duncan and coworkers.…”
Section: Introductionmentioning
confidence: 99%